The Role of Second-Line Leadership Development in Achieving Competitive Advantage: Evidence from UAE - AI Awani, Nasser Mohammed; Mohamad, Abu Dardaa (International Review of Management and Marketing, 2026)
This study investigates the role of second-line leadership development in achieving competitive advantage within the Federal Authority for Identity, Citizenship, Customs, and Port Security (ICP) in the United Arab Emirates. Using a descriptive–analytical approach, data were collected through a questionnaire distributed to a random sample of 214 employees, determined according to the Krejcie and Morgan table. Second-line leadership development was measured through development, empowerment, and motivation, while competitive advantage was assessed through service quality, innovation, and operational efficiency. The results indicate a high level of leadership development and competitive advantage within ICP. Regression analysis reveals a statistically significant positive effect of second-line leadership development on competitive advantage, with leadership development exerting the strongest influence. The study highlights the strategic importance of developing second-line leaders to enhance institutional performance and sustainability in public sector organizations.